The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.neuroscience.2007.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Spinal N-methyl-d-aspartate receptors and nociception-evoked release of primary afferent substance P

Abstract: Dorsal horn NMDA receptors contribute significantly to spinal nociceptive processing through an effect postsynaptic to non-primary glutamatergic axons, and perhaps presynaptic to the primary afferent terminals. The present study sought to examine the regulatory effects of NMDA receptors on primary afferent release of SP, as measured by neurokinin 1 receptor (NK1r) internalization in the spinal dorsal horn of rats. The effects of intrathecal NMDA alone or in combination with D-serine (a glycine site agonist) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
(80 reference statements)
0
37
0
1
Order By: Relevance
“…Using NK 1 R internalization as a tool to evaluate SP release, we demonstrated that selective activation of either MOPRs or DOPRs was sufficient to abolish formalin-and capsaicin-induced SP release. Interestingly, it was observed by others that MOPR agonists can decrease NK 1 R internalization induced by paw compression (Kondo et al, 2005) or intraplantar formalin (Nazarian et al, 2008). Similarly, Kondo et al (2005) have also observed DOPR-mediated inhibition of mechanical stimulus-induced NK 1 R internalization.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Using NK 1 R internalization as a tool to evaluate SP release, we demonstrated that selective activation of either MOPRs or DOPRs was sufficient to abolish formalin-and capsaicin-induced SP release. Interestingly, it was observed by others that MOPR agonists can decrease NK 1 R internalization induced by paw compression (Kondo et al, 2005) or intraplantar formalin (Nazarian et al, 2008). Similarly, Kondo et al (2005) have also observed DOPR-mediated inhibition of mechanical stimulus-induced NK 1 R internalization.…”
Section: Discussionmentioning
confidence: 86%
“…Following activation of primary afferent fibers by formalin and capsaicin, SP is released in the superficial laminae of the spinal cord, where it binds to and activates NK 1 R. Upon activation, NK 1 Rs are rapidly internalized (Mantyh et al, 1995;Abbadie et al, 1997;Marvizó n et al, 2003;Nazarian et al, 2008). NK 1 R internalization can therefore be used as an indication of SP release.…”
Section: Formalin-and Capsaicin-induced Nk 1 R Internalizationmentioning
confidence: 99%
“…Studies in dorsal horn neurons have established that activation of presynaptic NMDA receptors on the central terminals of peptidergic primary afferents causes an increased release of SP after dorsal root stimulation or administration of capsaicin (Afrah et al 2001;Liu et al 1997;Malcangio et al 1998;Marvizon et al 1997; but see Nazarian et al 2008). A similar mechanism may be invoked in the RVM in which synaptically released glutamate acts at presynaptic NMDA receptors on SP-containing afferents to RVM neurons.…”
Section: Mechanisms Of Facilitation In Type 1 and Type 2 Neuronsmentioning
confidence: 99%
“…24 Previous reports on NMDA and SP interaction suggest a regulatory role of NMDA in SP release which was also observed peripherally. [25][26][27] We can therefore speculate that the increased NMDAR1 levels have a role in SP elevation observed in tendinosis, however, interventional studies are essential in order to draw certain conclusions.…”
Section: Discussionmentioning
confidence: 99%